2018
DOI: 10.1016/j.susc.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of healed N-vacancy defective BC2N sheet and nanotube by NO molecule in oxidation of NO and CO gas molecules

Abstract: The role of healed N-vacancy defective BC 2 N sheet and nanotube by NO molecule in oxidation of NO and CO gas molecules,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Yang et al 28 and Su et al 29 reported the effective adsorption of different volatile and toxic gases on Al x @C 2 N. Furthermore, strong adsorption of NH 3 was observed on Al@MoS 2 30 as compared to that of the host ML. Overall, doping of an Al atom in 2D materials can be considered as a promising method to improve the adsorption ability of 2D materials 22–38 towards various gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 28 and Su et al 29 reported the effective adsorption of different volatile and toxic gases on Al x @C 2 N. Furthermore, strong adsorption of NH 3 was observed on Al@MoS 2 30 as compared to that of the host ML. Overall, doping of an Al atom in 2D materials can be considered as a promising method to improve the adsorption ability of 2D materials 22–38 towards various gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The vacancies and defects on the f-BNNT surface caused as a result of the hydroxylation process play a dual role in the catalytic process. First, the defects in f-BNNT induce a strong interaction between PGM nanoparticles and the f-BNNT surface, leading to an increase in the overall electronic effect in the PGM/f-BNNT interface, thereby causing better charge transfer and, hence, improved catalytic activity. , Second, these defect sites also improve the adsorption properties for NO and CO molecules, leading to a decrease in their activation energy, thereby facilitating the conversion process. , Taking into account the experimental and theoretical studies conducted to study the NO reduction by CO using a PGM-based catalyst, a higher catalytic activity for the PGM/BNNT catalyst can be successfully deduced. Both BNNT and PGM nanoparticle catalysts are well-known for the adsorption and activation of NO/CO. , The principle studies of CO and NO adsorption on a transition-metal (TM)-doped (8, 0) boron nitride nanotube reveal that the adsorption of gas molecules on metal-doped BNNT leads to activation and enhanced charge transfer, resulting in a strong chemical interaction of both CO and NO molecules with TM-doped BNNT .…”
Section: Resultsmentioning
confidence: 99%
“…26,46 Second, these defect sites also improve the adsorption properties for NO and CO molecules, leading to a decrease in their activation energy, thereby facilitating the conversion process. 59,60 Taking into account the experimental and theoretical studies conducted to study the NO reduction by CO using a PGM-based catalyst, 61−63 a higher catalytic activity for the PGM/BNNT catalyst can be successfully deduced. Both BNNT and PGM nanoparticle catalysts are well-known for the adsorption and activation of NO/CO.…”
Section: Stability Of the Pgm/f-bnnt Catalyst For Reduction Of No By Comentioning
confidence: 99%
“…The results showed that this study might be helpful in purifying the defective BCN nanostructures as well as removing toxic gases (such as NO and CO). 133 Yadav et al reported biomedical application of BCN sheets with theoretical aspects using DFT. Aspirin adsorption on BCN sheets and its HER activity was explored.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…The results showed that this study might be helpful in purifying the defective BCN nanostructures as well as removing toxic gases (such as NO and CO). 133…”
Section: Properties Of Boron Carbon Nitridementioning
confidence: 99%